Evaluation of Adjunctive Photobiomodulation (PBMT) for COVID-19 Pneumonia via Clinical Status and Pulmonary Severity Indices in a Preliminary Trial - Vetrici MA; Mokmeli S; Bohm AR; Monici M; Sigman SA (Dove Medical Press, 2021)
Mariana A Vetrici,1,* Soheila Mokmeli,2,* Andrew R Bohm,3 Monica Monici,4 Scott A Sigman5,* 1Department of Biological Sciences, University of Lethbridge, Lethbridge, AB, Canada; 2Training Institute, Canadian Optic and Laser Center, Victoria, BC, Canada; 3Department of Orthopedics, Lenox Hill Hospital, New York, NY, USA; 4ASA Campus J.L., ASA Res. Division – Department of Experimental and Clinical Biomedical Sciences, University of Florence, Florence, Italy; 5Department of Orthopedics, Lowell General Hospital, Lowell, MA, 01863, USA*These authors contributed equally to this workCorrespondence: Scott A SigmanDepartment of Orthopedics, Lowell General Hospital, 295 Varnum Avenue, Lowell, MA, 01863, USATel +1 978 856 7676Email sasigmanmd@icloud.comPurpose: Evidence-based and effective treatments for COVID-19 are limited, and a new wave of infections and deaths calls for novel, easily implemented treatment strategies. Photobiomodulation therapy (PBMT) is a well-known adjunctive treatment for pain management, wound healing, lymphedema, and cellulitis. PBMT uses light to start a cascade of photochemical reactions that lead to local and systemic anti-inflammatory effects at multiple levels and that stimulate healing. Numerous empirical studies of PBMT for patients with pulmonary disease such as pneumonia, COPD and asthma suggest that PBMT is a safe and effective adjunctive treatment. Recent systematic reviews suggest that PBMT may be applied to target lung tissue in COVID-19 patients. In this preliminary study, we evaluated the effect of adjunctive PBMT on COVID-19 pneumonia and patient clinical status.Patients and Methods: We present a small-scale clinical trial with 10 patients randomized to standard medical care or standard medical care plus adjunctive PBMT. The PBMT group received four daily sessions of near-infrared light treatment targeting the lung tissue via a Multiwave Locked System (MLS) laser. Patient outcomes were measured via blood work, chest x-rays, pulse oximetry and validated scoring tools for pneumonia.Results: PBMT patients showed improvement on pulmonary indices such as SMART-COP, BCRSS, RALE, and CAP (Community-Acquired Pneumonia questionnaire). PBMT-treated patients showed rapid recovery, did not require ICU admission or mechanical ventilation, and reported no long-term sequelae at 5 months after treatment. In the control group, 60% of patients were admitted to the ICU for mechanical ventilation. The control group had an overall mortality of 40%. At a 5-month follow-up, 40% of the control group experienced long-term sequelae.Conclusion: PBMT is a safe and effective potential treatment for COVID-19 pneumonia and improves clinical status in COVID-19 pneumonia.Keywords: COVID-19, low-level laser therapy, pneumonia, SMART-COP, BCRSS, RALE